Supporting cost-effective watershed management strategies for Chesapeake Bay using a modeling and optimization framework. (October 2021) - Kaufman, Daniel E.; Shenk, Gary W.; Bhatt, Gopal; Asplen, Kevin W.; Devereux, Olivia H.; Rigelman, Jessica R.; Ellis, J. Hugh; Hobbs, Benjamin F.; Bosch, Darrell J.; Van Houtven, George L.; McGarity, Arthur E.; Linker, Lewis C.; et al.
Abstract: Extensive efforts to adaptively manage nutrient pollution rely on Chesapeake Bay Program's (Phase 6) Watershed Model, called Chesapeake Assessment Scenario Tool (CAST), which helps decision-makers plan and track implementation of Best Management Practices (BMPs). We describe mathematical characteristics of CAST and develop a constrained nonlinear BMP-subset model, software, and visualization framework. This represents the first publicly available optimization framework for exploring least-cost strategies of pollutant load control for the United States' largest estuary. The optimization identifies implementation options for a BMP subset modeled with load reduction effectiveness factors, and the web interface facilitates interactive exploration of >30, 000 solutions organized by objective, nutrient control level, and for 200 counties. We assess framework performance and demonstrate modeled cost improvements when comparing optimization-suggested proposals with proposals inspired by jurisdiction plans. Stakeholder feedback highlights the framework's current utility for investigating cost-effective tradeoffs and its usefulness as a foundation for future analysis of restoration strategies. Graphical abstract: Image 1 Highlights: Software framework finds low-cost management strategies in watershed model. Optimization requirements shaped by local and state stakeholder engagement. Non-linear optimization based on simulation structure for BMP subset. Web interface for optimization results allows solution exploration by stakeholders.